2014
DOI: 10.1371/journal.pone.0107430
|View full text |Cite
|
Sign up to set email alerts
|

Gameplay as a Source of Intrinsic Motivation in a Randomized Controlled Trial of Auditory Training for Tinnitus

Abstract: BackgroundPrevious studies of frequency discrimination training (FDT) for tinnitus used repetitive task-based training programmes relying on extrinsic factors to motivate participation. Studies reported limited improvement in tinnitus symptoms.PurposeTo evaluate FDT exploiting intrinsic motivations by integrating training with computer-gameplay.MethodsSixty participants were randomly assigned to train on either a conventional task-based training, or one of two interactive game-based training platforms over six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 60 publications
0
39
0
2
Order By: Relevance
“…The meta-analysis used anonymised data that had been collected as part of various research studies led by the National Institute for Health Research (NIHR) Nottingham Hearing Biomedical Research Unit (BRU) conducted between 2009 and 2014. Because of the meta-analytic nature of this study it was not subject to a specific ethical approval, but for the individual research studies themselves written informed consent had been given by all participants and the studies had been approved by the following local National Health Service (NHS) Ethics Committees: Derbyshire [ 26 ]; East Midlands—Nottingham 1 [ 27 , 28 ]; East Midlands—Nottingham 2 [ 29 ], and East Midlands—Derby (Mohamad, personal communication). Sponsorship for all research studies was provided by Nottingham University Hospitals (NHS) Trust.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The meta-analysis used anonymised data that had been collected as part of various research studies led by the National Institute for Health Research (NIHR) Nottingham Hearing Biomedical Research Unit (BRU) conducted between 2009 and 2014. Because of the meta-analytic nature of this study it was not subject to a specific ethical approval, but for the individual research studies themselves written informed consent had been given by all participants and the studies had been approved by the following local National Health Service (NHS) Ethics Committees: Derbyshire [ 26 ]; East Midlands—Nottingham 1 [ 27 , 28 ]; East Midlands—Nottingham 2 [ 29 ], and East Midlands—Derby (Mohamad, personal communication). Sponsorship for all research studies was provided by Nottingham University Hospitals (NHS) Trust.…”
Section: Methodsmentioning
confidence: 99%
“…All participants were assessed prior to any intervention as part of the eligibility screening or the baseline evaluation and so our dataset included data from people who had been excluded from the research study according to its specific eligibility criteria, as well as those who had been enrolled as a subject. The participants were: 82 participants from a randomised controlled study of auditory training using a computerised listening assessment platform [ 26 ]; 294 participants from a randomised controlled trial of a commercial tinnitus device [ 27 ]; 64 participants from a controlled study of auditory training using a computerised gameplay platform [ 29 ]; 60 participants from a prospective evaluation of hearing aid benefit for tinnitus with brain imaging as one of the secondary outcome measures [ 28 ], and 174 participants from an cross-sectional study evaluating the relationship between tinnitus and cognition (ongoing). This gave us a total of 674 participant records.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from this study did point to an attentional deficit among tinnitus subjects but one that suggested a difficulty in the executive control of attention (i.e., the ability to focus on task relevant information and inhibit processing of irrelevant information) rather than in the selective attention component. Interestingly, a recent study by Hoare et al ( 89 ) also found no correlation between tinnitus handicap and performance on a visual version of a selective attention task as measured by The Test of Everyday Attention ( 80 ). However, as these studies assessed selective attention in the visual domain, they would not have been sensitive to impairments in the auditory modality.…”
Section: Evaluating the Scientific Evidencementioning
confidence: 98%
“…There was no significant change in tinnitus handicap, but baseline THI scores were relatively low. Hoare et al ( 89 ) administered a number of frequency discrimination training auditory games designed to interrupt tinnitus, possibly by diverting attention away from the tinnitus sound and toward an externalized sound source. However, the training had no impact on performance on an auditory sustained attention task as measured by The Test of Everyday Attention ( 80 ).…”
Section: Evaluating the Scientific Evidencementioning
confidence: 99%